THE PRINCIPAL’S LEADERSHIP STYLE IN IMPROVING TEACHER PERFORMANCE - Jon Helmi (AL-ISHLAH: Jurnal Pendidikan, 2019)
This study aims to determine the effect of the principal's leadership style on teacher performance. This research is a qualitative descriptive study. The location of the study was conducted in MTs Asy-syafi’iyah Pinggir, Bengkalis Regency, Riau. The subjects of this research are leadership directing and teacher performance. The objects of research are the teacher and the principal. In this case the researcher took a sample of 1 principal and 17 teachers. The researcher uses a total sampling technique or takes all subjects as a sample. To capture the data in this study, the researcher use several techniques, namely observation, interviews, questionnaires, and literature review. The results showed that the implementation of leadership style influenced the quality of education in MTs Asy-Syafi'iyah Pinggir. The leadership style is often used by principals in MTs Asy-Syafi’iyah Pinggir is democratic leadership. Democratic leadership style is the style of leader who gives broad authority to subordinates. Whenever there is a problem always include subordinates as a whole team. In a democratic leadership style the leader provides a lot of information about the tasks and responsibilities of his subordinates. Teacher performance in MTs Asy-Syafi'iyah Pinggir that the performance of a teacher can be improved if there is a match between work and his expertise, as well as the placement of teachers in their assignments.